THE RELATIONSHIP OF PREGNANT WOMEN'S KNOWLEDGE WITH THE FREQUENCY OF ANTENATAL CARE VISITS IN THE INDEPENDENT PRACTICE OF MIDWIFERES L KEDUNG SALAM KARAWANG REGENCY - Soelistiawaty, Indah; Balwiah, Rida (Jurnal Delima Harapan, 2025)
Background: Antenatal care services are health services provided by health workers to a pregnant woman during her pregnancy to ensure that pregnancy and childbirth do not pose a negative risk to her and her baby. Objective: To determine the relationship between knowledge of pregnant women and the frequency of antenatal care visits at PMB "L" Kedung Salam, Karawang Regency in 2024. Method: This research uses quantitative methods, analytical descriptive and a cross-sectional design approach. The sampling technique used total sampling involving 50 pregnant women in the second trimester and third trimester. The independent variable is pregnant women's knowledge about antenatal care examinations, and the dependent variable is the frequency of antenatal care examination visits. Data was obtained using primary data using a questionnaire and looking at the antenatal care (KIA) visit notebook. Results: more than half of pregnant women had less knowledge, 26 people (52%), and more than half of pregnant women with irregular criteria, 27 people (54%). The results of the chi square statistical test show a p value of 0.016 <0.05, which means there is a relationship between knowledge of pregnant women and the frequency of Antenatal Care visits at PMB L Kedung Salam, Karawang Regency in 2024. Conclusion: Pregnant women's knowledge has a significant influence on the frequency of Antenatal Care visits. It is important to increase the knowledge of pregnant women through effective education regarding the benefits and importance of Antenatal Care examinations to ensure a healthy and safe pregnancy.